2011
DOI: 10.1002/jbmr.473
|View full text |Cite
|
Sign up to set email alerts
|

Optimal monitoring time interval between DXA measures in children

Abstract: Purpose The monitoring time interval (MTI) is the expected time in years necessary to identify a change between two measures that exceeds the measurement error. Our purpose was to determine MTI values for dual-energy X-ray absorptiometry (DXA) scans in normal healthy children according to age, sex, and skeletal site. Methods 2014 children were enrolled in the Bone Mineral Density in Childhood Study and had DXA scans of the lumbar spine, total hip, non-dominant forearm, and whole body. Measurements were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 19 publications
(47 reference statements)
4
53
0
Order By: Relevance
“…The "least significant change" refers to the smallest percentage difference in measurements that exceeds the variability or "noise" from repeated measurements. 24 In densitometry centers that are able to perform a precision study, a least significant change of 3% or less usually can be achieved. 24 However, some hospital radiation safety committees prohibit DXA centers from carrying out these protocols.…”
Section: Interpreting Longitudinal Datamentioning
confidence: 44%
See 1 more Smart Citation
“…The "least significant change" refers to the smallest percentage difference in measurements that exceeds the variability or "noise" from repeated measurements. 24 In densitometry centers that are able to perform a precision study, a least significant change of 3% or less usually can be achieved. 24 However, some hospital radiation safety committees prohibit DXA centers from carrying out these protocols.…”
Section: Interpreting Longitudinal Datamentioning
confidence: 44%
“…24 In densitometry centers that are able to perform a precision study, a least significant change of 3% or less usually can be achieved. 24 However, some hospital radiation safety committees prohibit DXA centers from carrying out these protocols. It should also be recognized that interval growth changes and accompanying increases in bone size make it more difficult to differentiate true increases in density from changes in areal BMD that are related to growth.…”
Section: Interpreting Longitudinal Datamentioning
confidence: 44%
“…A recent study demonstrated that precision error of DXA scans varies with region of interest, age, and sex. For girls 17 years and younger, a monitoring time interval of 1 year enabled identifi cation of DXA changes that exceeded precision error [ 33 ]. Until further information becomes available, for most adolescents and young adults, it is reasonable to repeat the DXA measures after 1 year.…”
Section: When To Order Dxa Scanssupporting
confidence: 41%
“…Multiple studies with similar average treatment doses to those reported in this study have not demonstrated a decrease in the lumbar spine and hip BMD using dual X-ray absorptiometry (DXA) in pediatric or adult subjects [7][8][9][10][11]. A single-center study in [17][18][19][20][21][22][23][24][25] year-old men identified no significant difference in the spine or femoral neck BMD; however, a decrease in Ward's triangle BMD was described [2]. This finding in Ward's triangle is of dubious clinical significance, as this site is not used to diagnose osteoporosis in the pediatric years due to geometry changes during growth [12,13].…”
Section: Introductionsupporting
confidence: 41%
“…Six months is the minimum interval between scans, as recommended by the International Society of Clinical Densitometry (ISCD) [19]. However, a recent study evaluating DXA monitoring time interval (MTI) in a population of normal subjects suggests that in subjects from 12-17, MTI varied from 0.1 to 0.5 years [21]. This suggests that the expected BMD change in this study population would be detectable at 5.5 months.…”
Section: Discussionmentioning
confidence: 41%